Use of solid fat-tailored oleogels loaded with α-tocopherol as fat replacers to improve the nutritional profile of cookies - Peixoto, Vanessa Oliveira Di Sarli; Brito, Gabriela Baptista; Conte-Junior, Carlos Adam; Marinho, Thiago Oliveira; Nele, Márcio; Torres, Alexandre Guedes; Castelo-Branco, Vanessa Naciuk (Frontiers in Soft Matter, 2026)
IntroductionOleogels containing low candelilla wax (CLW) content (<2.5%) loaded with α-tocopherol mimic the rheological properties of butter, margarine, and partially hydrogenated fat. However, their use in food to enhance vitamin E intake remains unexplored. This study investigated CLW-based oleogels loaded with α-tocopherol, developed previously to replicate the rheological properties of butter (Obtr), margarine (Omgn), and partially hydrogenated fat (Ohgf), as full replacements for these fats in cookies.MethodsDoughs and cookies containing Obtr, Omgn, or Ohgf were assessed for instrumental color, rheological, textural, and baking properties. Principal component analysis (PCA) was applied to investigate the clustering and similarities between oleogel-based samples and their respective reference solid fats.ResultsDoughs with oleogels exhibited a darker surface and a weaker structure compared to those with solid fats. Cookies with oleogels were darker, softer, and less crispy than those made with solid fats. Cookies with OMGN exhibited a spread factor comparable to that of margarine, although other dimensional and textural parameters differed. PCA revealed no distinct clustering between the doughs containing oleogels and those with their respective solid fats (PC1 = 56.1%; PC2 = 28.9%). However, cookies containing oleogels clustered closely with those with partially hydrogenated fat (PC1 = 58.1%; PC2 = 38.8%), suggesting that reproducing the functional response of partially hydrogenated fat is more feasible than that of butter or margarine.ResultsTherefore, oleogels with low CLW content loaded with α-tocopherol present a promising alternative for replacing hydrogenated fats in cookies formulations.